TRPV1-target drugs for the treatment of orofacial pain - Andrade, Ana Cláudia Macedo; Molina Esquivel, Natalia; Goldschmied Rossel, Florencia; Benso, Bruna (Frontiers in Pharmacology, 2025)
Orofacial pain, encompassing sensory and emotional discomfort in the facial and oral regions, is a multifaceted condition that significantly impacts patients’ quality of life. This review focuses on the role of Transient Receptor Potential Vanilloid 1 (TRPV1) channels in modulating orofacial pain and new ligands targeting this receptor. TRPV1 channels act as key mediators of nociception, responding to stimuli such as temperature, pH changes, and capsaicin molecules. Recent advancements in TRPV1-targeted therapeutics, including natural, synthetic, and protein-based molecules, offer promising strategies for pain management. This review analyzed studies related to TRPV1-mediated pain inhibition, including seven clinical trials and preclinical investigations. The compounds studied in these works demonstrated pain relief, although adverse effects were reported. TRPV1-targeted molecules represent a novel avenue for developing innovative pharmacological interventions, addressing the limitations of current therapies, and improving patient outcomes in managing orofacial pain.